2021
DOI: 10.29219/fnr.v65.7526
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism and candidate compounds of aged citrus peel (chenpi) preventing chronic obstructive pulmonary disease and its progression to lung cancer

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is an important risk factor for developing lung cancer. Aged citrus peel (chenpi) has been used as a dietary supplement for respiratory diseases in China. Objective: To explore the mechanism and candidate compounds of chenpi preventing COPD and its progression to lung cancer. Methods: The active components and potential targets of chenpi were retrieved from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Disease-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Several studies have reported that HES can ameliorates anxiety and depression-like behaviors by enhancing Glo-1 and activating the Nrf2/ARE pathway in the brain of diabetic rats and high glucose cultured SH-SY5Y cells [19]. HES is also regarded as a natural product for the prevention and treatment of cancer [20,21]. Moreover, HES and its derivatives may improve complex central nervous system diseases such as Alzheimer's disease (AD) [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that HES can ameliorates anxiety and depression-like behaviors by enhancing Glo-1 and activating the Nrf2/ARE pathway in the brain of diabetic rats and high glucose cultured SH-SY5Y cells [19]. HES is also regarded as a natural product for the prevention and treatment of cancer [20,21]. Moreover, HES and its derivatives may improve complex central nervous system diseases such as Alzheimer's disease (AD) [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Silibinin, an active constitute of silymarin, could markedly reduce the production of fibrotic mediators in CS + LPS-exposed mice via suppression of TGF-β1/Smad 2/3 signaling ( Ko et al, 2017 ), as well as clearly decrease the pro-inflammatory mediators and airway mucus production expression in CS condensate-stimulated H292 cells and COPD mice model via the inhibition in ERK phosphorylation ( Park et al, 2016 ). Among dihydroflavones, Naringenin, hesperetin, and liquiritin apioside (LA) also exhibited positive effects on COPD, among which hesperetin could not only effectively alleviate inflammation and oxidative stress responses in CES-induced COPD mice by virtue of NAD-dependent protein deacetylase sirtuin-1(SIRT1)/PGC-1α/NF-κB signaling axis ( Wang et al, 2020 ), but also suppress the protein expression of AKT1, IL6, VEGFA, and MMP9 and up-regulate TP53 to reduce the risk of COPD progressing to lung cancer ( Zhou et al, 2021 ). Besides, LA offered protection to lung epithelial cell from CS-induced injuries by inhibiting the transforming growth factor- β (TGF-β) and tumor necrosis factor-α (TNF-α) expression and increasing anti-oxidative levels of glutathione (GSH) ( Guan et al, 2012 ).…”
Section: Flavonoidmentioning
confidence: 99%
“…Hesperidin is a multi-effect citrus flavone, and the most abundant polyphenol in citrus fruits and traditional Chinese medicine [26,27]. Studies have confirmed that hesperidin has minimal or no side effects [28] and has an anti-cancer effect in a variety of cancers, such as gastric cancer [29,30], breast cancer [27], and lung cancer [31,32]. Although the role of hesperidin's anti-cancer activity in different cancer has been studied, limited work has been conducted on its role in MNNG-induced gastric cancer.…”
Section: Introductionmentioning
confidence: 99%